TiAl-based semi-finished material produced by reaction annealing of Ti/Al layered composite sheets. (March 2022) - Pukenas, A.; Chekhonin, P.; Scharnweber, J.; Chulist, R.; Oertel, C.-G.; Freudenberger, J.; Skrotzki, W.
Abstract: In this study multi-layered Ti/Al sheets prepared by accumulative roll bonding (ARB) underwent a two-step heat treatment (HT) to form intermetallic compounds. The microstructure and crystal structure of the samples were examined by scanning and transmission electron microscopy as well as energy-dispersive X-ray spectroscopy and synchrotron diffraction. In the first solid-state reaction annealing step, Ti-rich ARB samples containing 60 at% Ti and 40 at% Al were held at 600 °C for 12 h under a uniaxial pressure between 0 MPa and 50 MPa applied along the normal direction of the sheets. At this stage, Al is completely consumed by forming mainly Al-rich intermetallic phases and to a lower extent other titanium aluminides such as Ti3 Al and TiAl. In the second step, high-temperature annealing produces TiAl and Ti3 Al as major phases during both pressureless annealing at 1100 °C, 1200 °C and 1300 °C and annealing under an uniaxial pressure of about 100 MPa at 1200 °C. Pore formation during the reaction annealing can be significantly reduced by the applied pressure. As a result, a TiAl-based semi-finished material was fabricated. Highlights: Multi-layered Ti/Al sheets prepared by accumulative roll bonding (ARB) underwent a two-step heat treatment. At 600 °C for 12 h under a uniaxial pressure Al is completely consumed by forming mainly Al-rich intermetallic phases. High-temperature annealing above 1100 °C with and without pressure produces TiAl and Ti3 Al as major phases. Pore formation during the reaction annealing can be significantly reduced by the applied pressure. As a result, a TiAl-based semi-finished material was fabricated.